Ghana Engaging the Private Sector in Education : SABER Pilot Country Report 2015 - Abdul-Hamid, Husein; Baum, Donald Rey; De Brular, Laura Lewis; Lusk-Stover, Oni; Tettey, Leslie Ofosu (World Bank, Washington, DC, 2017)
Systems approach for better education results (SABER) - engaging the private sector (EPS) research in Ghana has found that enrollment rates for primary and secondary education have increased significantly. At both the primary and secondary levels, quality, and equity remain challenges. The private sector plays an increasingly significant role in education at both levels. Based on a review of existing policies, SABER-EPS offers the following recommendations for Ghana to enhance private sector engagement in education and meet the challenges of access, quality, and equity: (1) strengthen policies to ensure independent private schools are more accountable for learning outcomes; (2) provide greater incentives to support a diverse number of private school providers while ensuring equitable access; and (3) encourage innovation in schools by ensuring greater flexibility in managing schools, services, and staff. This report presents an analysis of how effectively policies in Ghana engage the private sector in basic (primary and secondary) education. The report provides an overview of the SABER-EPS tool, followed by a description of the basic education system in Ghana that focuses on the private sector and government policies related to the private provision of education. The report then benchmarks Ghana’s policy environment utilizing the SABER-EPS framework and offers policy options to enhance access and learning for all children in primary and secondary school.